Acute modification in plasma lipid levels in ultramarathon runners. Issue 17 (1st September 2016) - Emed, Luiz Gustavo Marin; Passaglia, Daniela Gunther; Guerios, Surya T.; João, Paula G. D.; Moser, André I. S.; Abdalla, Dulcinéia S. P.; Guarita-Souza, Luis Cesar; Mikilita, Emanuella Stella; Baena, Cristina Pellegrino; da Costa, Ana Beatriz Brenner Affonso; Faria-Neto, José Rocha
ABSTRACT: We aimed to evaluate the effects of a 24-h ultramarathon, an aerobic test of high physical load, on lipid profile and apolipoproteins B (ApoB) and A1 (ApoA1) levels, minimally modified low-density lipoprotein (LDL), and oxidised LDL. Prospective evaluation of 16 male athletes who participated in an ultramarathon run, where the objective was to run the greatest distance possible in 24 h. Fourteen participants completed the run. The mean distance achieved was 133.1 km (maximum of 169.6 km). There was a trend in reduction of triglycerides and total cholesterol ( P  = 0.06 and 0.05, respectively), without significant modifications in high-density lipoprotein, LDL and ApoA1 levels ( P  = 0.16; 0.55 and 0.67). There was a marked reduction in ApoB levels ( P  < 0.001), correlated directly to the distance covered (Pearson R  = 0.68). Accordingly, an increase in the LDL/ApoB ratio was observed. The stress of this physical activity was not associated to an increase in minimally modified LDL or oxidised LDL. Lipid profile levels were not acutely altered by prolonged physical activity. Similarly, there was no evidence of greater oxidation of LDL over a 24-h period of physical activity. The reduction in ApoB was directly proportional to the distance covered, suggesting an acute positive change in phenotype of LDL molecules.